Tumor Necrosis Factor-α-Induced Protein 8-Like 2 Negatively Regulates Innate Immunity Against RNA Virus by Targeting RIG-I in Macrophages - Zou, Ziqi (Front Immunol, 2021)
A systematic and flexible immunoregulatory network is required to ensure the proper outcome of antiviral immune signaling and maintain homeostasis during viral infection. Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2), a novel immunoregulatory protein, has been extensively studied in inflammatory response, apoptosis, and cancer. However, the function of TIPE2 in antiviral innate immunity is poorly clarified. In this study, we reported that the expression of TIPE2 declined at the early period and then climbed up in macrophages under RNA virus stimulation. Knockout of TIPE2 in the macrophages enhanced the antiviral capacity and facilitated type I interferon (IFN) signaling after RNA viral infection both in vitro and in vivo. Consistently, overexpression of TIPE2 inhibited the production of type I IFNs and pro-inflammatory cytokines, and thus promoted the viral infection. Moreover, TIPE2 restrained the activation of TBK1 and IRF3 in the retinoic acid inducible gene-I (RIG-I)-like receptors (RLR) signaling pathway by directly interacting with retinoic acid inducible gene-I (RIG-I). Taken together, our results suggested that TIPE2 suppresses the type I IFN response induced by RNA virus by targeting RIG-I and blocking the activation of downstream signaling. These findings will provide new insights to reveal the immunological function of TIPE2 and may help to develop new strategies for the clinical treatment of RNA viral infections.